1994
DOI: 10.1177/030089169408000611
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Study of Immunotherapy with Low-Dose Subcutaneous Interleukin-2 plus Melatonin Vs Chemotherapy with Cisplatin and Etoposide as First-Line Therapy for Advanced Non-Small Cell Lung Cancer

Abstract: Aims and Background The theraputic role of chemotherapy in advanced non-small cell lung cancer (NSCLC) is controversial because of its potentially detrimental action on host anticancer defenses. On the contrary, IL-2 would seem to prolong survival time by improving the immune status, even though it is generally less effective in determining tumor regression in NSCLC. Our previous studies have suggested the possibility of increasing tumor sensitivity to IL-2 by concomitant administration of immunomodulating neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 10 publications
0
23
0
1
Order By: Relevance
“…Other trials have used melatonin with interleukin II with benefit. These trials need to be repeated in larger numbers and by multiple investigators before widespread use of melatonin [77,[79][80][81][82][83][84][85][86].…”
Section: Melatoninmentioning
confidence: 99%
“…Other trials have used melatonin with interleukin II with benefit. These trials need to be repeated in larger numbers and by multiple investigators before widespread use of melatonin [77,[79][80][81][82][83][84][85][86].…”
Section: Melatoninmentioning
confidence: 99%
“…After referring to full texts, we removed 275 studies that did not meet the selection criteria (Figure 1). As a result, 12 studies [16], [21][31] that included a total of 3134 patients were selected for meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Although six studies did not describe OS [23] or PFS [16], [21], [22], [24], [26] and four studies did not provide the number of patients in CR and/or PR rates [22], [26], [29], [31], all 12 studies were open-labeled and randomized. They mentioned the concealment of allocation clearly in the randomization process, and provided the number of patients who withdrew from the trials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several clinical studies have shown that MLT therapy, alone or in combination with IL-2, significantly decreases the progression of various tumors, e.g., carcinomas (136), melanoma (135), renal (133,135), lung (135)(136)(137)(138), and breast tumors (139)(140)(141). Cancer patients, who were unable to tolerate the IL-2 therapy alone and who did not respond to standard anti-cancer chemotherapies, were shown to have increased IL-2 tolerance, and they exhibited an effective antitumor defense response when they were treated with a combination of MLT and IL-2 (134,135,(142)(143)(144)(145)(146)(147)(148). Although the exact mechanism responsible for the anti-neoplastic action of MLT has not been determined, it has been suggested that MLT mediates its effect on hematopoietic progenitor cells, i.e., it increases the number of the granulocyte macrophage-colony forming unit (34,117).…”
Section: Immunomodulatory Effect Of Melatoninmentioning
confidence: 99%